Analog laboratory experiments of fracture networks formed due to forced folding and pore fluid overpressure - Michael Warsitzka; Nina Kukowski; Franz May (PANGAEA, 2022)
Forced folding of a low-permeable, competent sediment layer in response to magmatic sill intrusion, remobilisation of fluidized sand or fluid overpressure in underlying porous reservoir formations can cause the formation of complex fracture networks. The opening modes and geometries of these fractures affect the bulk permeability of the cover layer and, thus, are crucial for understanding fluid flow processes in sedimentary basins. We carried out analog experiments in the laboratory of the Institute of Geosciences, Friedrich Schiller University Jena (project: Mobilization of Unconsolidated Sediments Related to CO2 Storage) to simulate the evolution of fracture networks during forced folding, its differences between a 2D and 3D modelling approach and its variability depending on the rheological stratification of the cover. To produce a fluid overpressure in the layered analog materials, air was injected from the base of the layering and additionally through a point-like needle valve penetrating into the lowermost layer with a stepwise increasing air flux (Q). Pressure sensors recorded the air pressure at the base of the reservoir layer and in the needle valve. The experiments were monitored with a digital SLR camera and analyzed by the digital image correlation software DaVis 10.0 (LaVision GmbH) to calculate displacement and strain patterns in the analog materials. Furthermore, a fracture analysis was performed for which we measured length and dips or strikes, respectively, in the side view of the 2D experiments and in top view in the 3D experiments. Based on these data, opening modes of the fractures were determined and statistical analyses were applied. The outcomes of these analyses are shown in rose diagram and histograms. The data set presented here includes: 1) Original data: -PhotosOriginal.zip: Photos of the experimental evolution -FractureData.zip: Measured lengths and dips (from side views of the 2D experiments) or strikes (from top view of the 3D experiments) of individual fracture segments -PneumaticData.zip: Data of volumetric air flow rate (Q) and air pressure (P) recorded during the experiments 2) Analyzed data: -DigitalImageCorrelation.zip: Results of digital image correlation including edited photographs as well as data and plots of the displacement vector fields -SurfaceDisplacement.zip: Edited photos and a Python script for analyzing the vertical displacements of the experimental surface. -RoseDiagrams.zip: Rose diagrams plotting the dips or strikes, respectively, of the fracture segments -Histograms.zip: Histogram showing the abundance of fracture segments along the vertical z-axis in the 2D experiments or along the horizontal x and y axes in the 3D experiments Detailed descriptions of the experiments, method and results can be found in Warsitzka, et al. (2022) to which this data set is supplement.